Cardiovascular Magnetic Resonance for Rejection Surveillance After Cardiac Transplantation. Issue 25 (27th May 2022) - Anthony, Chris; Imran, Muhammad; Pouliopoulos, Jim; Emmanuel, Sam; Iliff, James; Liu, Zhixin; Moffat, Kirsten; Ru Qiu, Min; McLean, Catriona A.; Stehning, Christian; Puntmann, Valentina; Vassiliou, Vass; et al.
Abstract : Background: Endomyocardial biopsy (EMB) is the gold standard method for surveillance of acute cardiac allograft rejection (ACAR) despite its invasive nature. Cardiovascular magnetic resonance (CMR)–based myocardial tissue characterization allows detection of myocarditis. The feasibility of CMR-based surveillance for ACAR-induced myocarditis in the first year after heart transplantation is currently undescribed. Methods: CMR-based multiparametric mapping was initially assessed in a prospective cross-sectional fashion to establish agreement between CMR- and EMB-based ACAR and to determine CMR cutoff values between rejection grades. A prospective randomized noninferiority pilot study was then undertaken in adult orthotopic heart transplant recipients who were randomized at 4 weeks after orthotopic heart transplantation to either CMR- or EMB-based rejection surveillance. Clinical end points were assessed at 52 weeks. Results: Four hundred one CMR studies and 354 EMB procedures were performed in 106 participants. Forty heart transplant recipients were randomized. CMR-based multiparametric assessment was highly reproducible and reliable at detecting ACAR (area under the curve, 0.92; sensitivity, 93%; specificity, 92%; negative predictive value, 99%) with greater specificity and negative predictive value than either T1 or T2 parametric CMR mapping alone. High-grade rejection occurred in similar numbers of patients in each randomized group (CMR, n=7; EMB, n=8; P =0.74). Despite similarities in immunosuppression requirements, kidney function, and mortality between groups, the rates of hospitalization (9 of 20 [45%] versus 18 of 20 [90%]; odds ratio, 0.091; P =0.006) and infection (7 of 20 [35%] versus 14 of 20 [70%]; odds ratio, 0.192; P =0, 019) were lower in the CMR group. On 15 occasions (6%), patients who were randomized to the CMR arm underwent EMB for clarification or logistic reasons, representing a 94% reduction in the requirement for EMB-based surveillance. Conclusions: A noninvasive CMR-based surveillance strategy for ACAR in the first year after orthotopic heart transplantation is feasible compared with EMB-based surveillance. Registration: HREC/13/SVH/66 and HREC/17/SVH/80. Australian New Zealand Clinical Trials Registry: ACTRN12618000672257.